Bibliometrics: Analysis of the Development of Desalination Membranes in the Past Decade to 2022 - Triadi, Hari Agung (Penerbit Goodwood, 2025)
Purpose: This study uses a bibliometric method to computational mapping analysis with VOSviewer to look at how chemical particle desalination membrane research has evolved. Methodology: By using the publish or perish reference manager tool, the Google Scholar database was queried for the article data. By using the phrase